Pan-African adakitic rocks from the Sør Rondane Mountains, East Antarctica - Owada, Masaaki; Toyoshima, Tsuyoshi; Shiraishi, Kazuyuki; Kagami, Hiroo (National Institute of Polar Research, 2006)
P(論文) The Sør Rondane Mountains (22°E -28°E ) are located in eastern Dronning Maud Land, East Antarctica, and consist of amphibolite to granulite facies metamorphic rocks and various intrusive rocks. Peak metamorphism took place during the Pan-African event. Considering the mode of occurrence and previously reported age data, felsic magma activity started at the waning stage of the metamorphism. In this study, we report on the petrogenesis of discordantly intruding post-tectonic pyroxene tonalite (Px tonalite) with adakitic composition. In addition, the petrogenesis of posttectonic biotite granite (Bt granite), of which the geochemical features are similar to high-K adakite in the collision zone, are reevaluated with reference to the Px granite. The initial Sr isotopic ratios (SrI) corrected to 525Ma of Px tonalite and Bt granite represent limited values (0.7037-0.7052) that are included within the SrI of the Proterozoic metatonalite corrected to the same age (525Ma). These Sr isotopic signatures combined with geochemical modeling suggest that chemical variation of Px tonalite and Bt granite can be explained by partial melting of the Proterozoic metatonalite with various degrees of melting, leaving garnet as a residual phase, subsequent to fractional crystallization and/or accumulation of specific phases. Taking the tectonic situation and geochemical signature into account, Px tonalite and Bt granite from the Sør Rondane Mountains are correlated to the collision zone adakite and represent the post-collision magmatism in the suture zone during the Gondwana formation of the Pan-African event. departmental bulletin paper